Isolation of Lignin from Sugarcane Bagasse as an Adsorbent for Chromium Ion - Berghuis, Nila Tanyela; Novianti, Nurul Fitri; Ratri, Paramita Jaya (UI Scholars Hub, 2023)
The waste generated in metal coating and leather tanning industries contribute to water pollution owing to the use of Cr metal in production processes. The utilization of lignin from natural base materials in the form of bagasse can reduce unwanted waste from production processes and adsorb Cr ion waste. In this study, lignin was successfully isolated from bagasse waste and then carbonized and applied in Cr metal absorption. Lignin and lignin carbon as an absorbent were characterized using Fourier-transform infrared spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The ability of bagasse lignin and carbon lignin to absorb Cr ion waste was evaluated by monitoring mass fluctuation, contact time, and pH. The optimal conditions for adsorption were determined as follows: 0.015 g, 90 min, and pH 6. The adsorption isotherm followed the Freundlich model, and the adsorption kinetics followed the pseudo-first-order model. Furthermore, adsorption thermodynamics showed that the reaction proceeded spontaneously, and the disorder degree increased in the adsorption system